The emerging relationship between mucosal-associated invariant T cell populations and the onset and progression of type 1 diabetes - Fraser, Devin R.; Stadnyk, Andrew W. (Frontiers in Immunology, 2025)
Type 1 diabetes (T1D) is a chronic autoimmune disorder characterized by autoreactive CD8+ T cells that destroy insulin-producing pancreatic β-cells. CD8+ T cells are unlikely to be the only cells involved in diabetes. Relatively recently described and still enigmatic, Mucosal-associated invariant T (MAIT) cells, innate-like T cells that recognize microbial-derived peptides, exist in the blood and tissues and are implicated in early immune responses. Immunological differences, some of which implicate MAIT cells, exist between individuals at different stages of T1D progression. This review explores the emerging relationship between gastrointestinal and pancreatic MAIT cell populations and the onset and progression of T1D. Early microbial colonization is critical for immune maturation, homeostasis, and MAIT cell development, and disruptions such as Caesarean delivery or antibiotic-induced dysbiosis correlate with increased T1D incidence. Diabetes progression in the diabetes-prone NOD mice is associated with reduced gut mucosal integrity, impairing the protective IL-17 and IL-22 responses of gut-resident MAIT cells and exacerbating systemic inflammation. MAIT cells recruited to the inflamed pancreas during T1D onset likely contribute to β-cell destruction through IFN-γ and granzyme B production. This hypothesis is supported by altered MAIT cell frequencies and phenotypes in individuals with T1D; MAIT cells are reduced in the blood of children recently diagnosed with T1D, potentially corresponding to pancreatic migration, while adults with long-term T1D have persistent, circulating MAIT cells with exhaustion markers. MAIT cells appear to have dual protective and pathogenic roles impacted by microbiome interactions. Understanding these relationships may inform non-invasive biomarkers for the disease.